Pengaruh Gaya Kepemimpinan Transformasional dan Pengembangan Karis Terhadap Kinerja Pegawai Toko Buku Gramedia Bintara Plaza - Lilis Rohayati (Jurnal Satya Mandiri Manajemen dan Bisnis, 2023)
ABSTRACT This research aims to determine the influence of Transformational Leadership and Career Development on the Performance of Gramedia Bintara Plaza Bookstore Employees. The research design uses quantitative causality. The data used is primary data collected through questionnaires. The population and sample in this study were 54 employees, the sampling technique used a saturated sample or census, the data analysis method used Multiple Liner Regression Analysis with SPSS 26 software. The results of the research were the positive and significant influence of Transformational Leadership and Character Development on the Performance of Gramedia Bookstore Employees Plaza NCO. Keywords: Transformational Leadership Style, Career Development, and Employee Performance